2010
DOI: 10.26719/2010.16.9.982
|View full text |Cite
|
Sign up to set email alerts
|

Role of shame in the stigmatization of people with human immunodeficiency virus: a survey of female college students in 3 Arab countries

Abstract: AIDS stigma is a challenge to controlling the HIV/AIDS epidemic especially in more conservative cultures. This study explored the impact of knowledge about HIV and AIDS, and the impact of shame, on the stigmatization of people living with HIV/AIDS in the Arab world. Survey data were collected from 277 female college students in 3 Arab countries: Kuwait, Bahrain and Jordan. Only in Bahrain was knowledge about HIV and AIDS inversely related to negative attitudes toward people with HIV/AIDS. AIDS-related shame, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…The only study of 277 female college students in three countries indicated that HIV knowledge among Bahraini students was associated with negative attitudes toward HIV-infected patients (19). To remove stigma and to contribute to HIV awareness, Bahrain Reproductive Health has approved a HIV/AIDS plan for workplaces.…”
Section: Resultsmentioning
confidence: 99%
“…The only study of 277 female college students in three countries indicated that HIV knowledge among Bahraini students was associated with negative attitudes toward HIV-infected patients (19). To remove stigma and to contribute to HIV awareness, Bahrain Reproductive Health has approved a HIV/AIDS plan for workplaces.…”
Section: Resultsmentioning
confidence: 99%
“…26 Seven quantitative studies were assessed to be of fair quality. [29][30][31][32][33][34][35] Although some of these studies had a sample representative of the target population, 29,31,35 poor reporting made it difficult to assess the risk of selection bias in two studies 30,33 and two studies used sampling strategies that had the potential to introduce bias. 32,34 Only two studies were judged to be of poor quality.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Studies on attitudes towards HIV/AIDS among Arabs show that they are by large negative. These include, for example, studies on university and college students fromYemen (Soffer, 2019), the Gaza Strip (Kanoa, AbuNada, El-Sakka, Kariri, & Al-Hindi, 2015), the United Arab Emirates (Haroun et al, 2016), as well as studies on women students from Kuwait, Bahrain and Jordan (Badahdah & Foote, 2010), nursing students from Saudi Arabia (Abolfotouh, Saleh, Mahfouz, Abolfotouh, & Al Fozan, 2013), dental students from Saudi Arabia (Al-Qahtani et al, 2019), Palestinian dentists (Kateeb, Amer, & Bajali, 2015), pharmacy students in Qatar (Black, Wilby, & Perepelkin, 2013), adolescents in Saudi Arabia (Bokhamseen et al, 2017), the general public in Bahrain (Janahi, Mustafa, Alsari, Al-Mannai, & Farhat, 2018) and in Israel (author).…”
Section: Introductionmentioning
confidence: 99%